Assessment of hydrogen storage in activated carbons produced from hydrothermally treated organic materials. (27th July 2016) - Schaefer, S.; Fierro, V.; Izquierdo, M.T.; Celzard, A.
Abstract: 12 activated carbons (ACs) were prepared by KOH activation using hydrochars as precursors. These hydrochars were prepared by hydrothermal carbonisation (HTC) of sucrose solutions at concentrations ranging from 0.2 to 1.6 mol L −1 . The KOH to hydrochar weight ratio ( W ) was varied from 1 to 5, and the activation temperature was set to 1023 K. ACs texture was assessed by nitrogen and carbon dioxide adsorption at 77 and 273 K, respectively; pore size distribution was calculated by using both isotherms and the SAIEUS© software. ACs with surface areas between 790 and 2240 m 2 g −1 were obtained. Hydrogen excess adsorption was determined at 298 K and pressures up to 10 MPa in a volumetric device, and the isosteric heat of adsorption ( Q st ) was calculated for four ACs, using hydrogen isotherms obtained at 278, 298 and 308 K. Potassium intercalation between graphitic planes was assumed to account for the high Q st values, 7–8 kJ mol −1 . Hydrogen uptake at 2 MPa was compared with hydrogen adsorption data of 38 other ACs reported in the open literature. Hydrogen adsorption fundamentally depends on micropore volume and preliminary HTC did not enhance hydrogen storage although it could be a good strategy for doping carbon with heteroelements. Highlights: High surface activated carbons were produced from hydrothermally treated sucrose. KOH activation allowed obtaining highly microporous activated carbons. High isosteric heats of adsorption, 7–8 kJ mol −1 were determined. Hydrogen adsorption fundamentally depends on micropore volume. Preliminary hydrothermal treatment did not enhance hydrogen storage.